Room response to frequency change and its relation to the pitch changes - RUTKOWSKI, L. (Archives of Acoustics, 1996)
When a signal of constant frequency is sent into a room and its frequency changes to a new value, then, beginning from this moment, in the room there will exist two signals with changing amplitudes (i.e. decreasing one with the old frequency value and an increasing one with a new frequency value). As result of these changes envelope and instantaneous frequency changes appear. These changes have a transient character and exist in a time interval that equals the room reverberation time. Instantaneous frequency and envelope changes are similar to those observed for beating. To describe these changes the modified IWAIF model [1, 2] is used that allows an attempt to evaluate the pitch change in time. It is found that the calculated pitch changes, predicted as an effect of the frequency change in the room, have a monothonical character and appear within the range from the initial frequency to the final one. The rate and character of the calculated predicted pitch changes depends on the amplitude ratio of the two signals, the value of the frequency difference and on the room reverberation time.